Research paradigms in education: A comparation between Foucault’s postmodernism, positivism, interpretivism and critical theory - Mbhiza, H. (South African Journal of Higher Education, 2024)
The concept of paradigm in research is one that many postgraduate students as well as emerging researchers find difficult to understand and apply in their research proposal and/or research writings. In recent seminars, I have observed that students in higher degrees find the concept of research paradigms, particularly the postmodern paradigm, as difficult to explain. This conceptual paper focuses on what Foucault (1970) refers to as “discursive formations” and discusses the constitutive elements of discursive formations are. The similarities and differences between Foucault’s view of knowledge and the views of knowledge held within positivism, interpretivism and critical theory are indicated as a way of making the paradigmatic language for these positions comprehensible. Foucault’s work (1970, “The Archaeology of Knowledge”) is used to look at the educational implications of postmodernism, helping to understand the processes of learning and teaching, as well as what is considered as educational knowledge.